CD14 and IL18 gene polymorphisms associated with colorectal cancer subsite risks among atomic bomb survivors - Hu, Yiqun (Hum Genome Var, 2015)
Colorectal cancer (CRC) is a common malignancy worldwide, and chronic inflammation is a risk factor for CRC. In this study, we carried out a cohort study among the Japanese atomic bomb (A-bomb) survivor population to investigate any association between immune- and inflammation-related gene polymorphisms and CRC. We examined the effects of six single-nucleotide polymorphisms of CD14 and IL18 on relative risks (RRs) of CRC. Results showed that RRs of CRC, overall and by anatomic subsite, significantly increased with increasing radiation dose. The CD14–911A/A genotype showed statistically significant higher risks for all CRC and distal CRC compared with the other two genotypes. In addition, the IL18–137 G/G genotype showed statistically significant higher risks for proximal colon cancer compared with the other two genotypes. In phenotype–genotype analyses, the CD14–911A/A genotype presented significantly higher levels of membrane and soluble CD14 compared with the other two genotypes, and the IL18–137 G/G genotype tended to be lower levels of plasma interleukin (IL)-18 compared with the other two genotypes. These results suggest the potential involvement of a CD14-mediated inflammatory response in the development of distal CRC and an IL18-mediated inflammatory response in the development of proximal colon cancer among A-bomb survivors.